Controllable synthesis of silicon/carbon microspheres alternating carbon and silicon shells for high-energy lithium-ion batteries. (10th November 2022) - Luo, Jinhua; Xu, Difa; Chen, Liang; An, Changsheng; Wang, Yanhong; Zhu, Hai; Feng, Wenhui; Li, Yanhua; Zhang, Shiying; Chen, Han
Highlights: The synthesis of microspheres with alternate carbon and silicon shells can be controlled. The microspheres with two carbon shells exhibited excellent electrochemical performance. The double-layer microspheres show smallest voluminal variation after 100 cycles. SCM-2 with compromise proportion for carbon and silicon remains intact after 100 cycles. The SCM-2//LiCoO2 full cell displays the best reversible electrochemical behavior. Abstract: The poor cycling stability and huge volume change of silicon during the charge/discharge processes have seriously hindered the extensive application. In order to deal with address various challenges, silicon/carbon microspheres (SCM) are designed via nonsynchronous nucleation, hydrothermal coupling method and magnesium thermal reduction method. The silicon/carbon microspheres with two carbon shells (SCM-2) delivers the most enhanced initial charge capacity of 2455 mAh g –1 at 0.1 C, and reveals the highest specific capacity of 2178 mAh g –1 after 200 cycles and capacity retention of 98% after 500 cycles at 2 C. The SCM-2//LiCoO2 full cell can maintain high capacity of 159.2 mAh g –1 and no capacity decay after 500 cycles at 0.1 C. It is demonstrated that the fabrication for silicon/carbon microspheres is a convenient and effective strategy to resolve the practical application silicon anode material in lithium-ion batteries. Graphical abstract: Image, graphical abstract